Marine-derived fungus Aspergillus cf. tubingensis LAMAI 31: a new genetic resource for xylanase production - dos Santos, Juliana A. [UNESP]; Vieira, Juliana M. F. [UNESP]; Videira, Alexandre [UNESP]; Meirelles, Lucas A. [UNESP]; Rodrigues, André [UNESP]; Taniwaki, Marta H.; Sette, Lara D. [UNESP] (Springer Nature, 2016)
Marine-derived fungi have been reported as relevant producers of enzymes, which can have different properties in comparison with their terrestrial counterparts. The aim of the present study was to select from a collection of 493 marine-derived fungi the best producer of xylanase in order to evaluate the enzymatic production under different conditions. A total of 112 isolates produced xylanase in solid medium containing xylan as the carbon source, with 31 of them able to produce at least 10 U/mL of the enzyme. The best production (49.41 U/mL) was achieved by the strain LAMAI 31, identified as Aspergillus cf. tubingensis. After confirming the lack of pathogenicity (absence of ochratoxin A and fumonisin B2 production) this fungus was submitted to the experimental design in order to evaluate the effect of different variables on the enzymatic production, with the aim of optimizing culture conditions. Three experimental designs (two Plackett–Burman and one factorial fractional) were applied. The best condition for the enzymatic production was defined, resulting in an increase of 12.7 times in comparison with the initial production during the screening experiments. In the validation assay, the peak of xylanase production (561.59 U/mL) was obtained after 96 h of incubation, being the best specific activity achieved after 72 h of incubation. Xylanase from A. cf. tubingensis LAMAI 31 had optimum pH and temperature at 5.0 and 55 °C, respectively, and was shown to be stable at a range of 40–50 °C, and in pH from 3.6 to 7.0. Results from the present work indicate that A. cf. tubingensis LAMAI 31 can be considered as a new genetic resource for xylanase production.
Keywords: Experimental design; Marine biotechnology; Marine-derived fungi; Xylanase